Voluntary wheel running exercise rescues behaviorally-evoked acetylcholine efflux in the medial prefrontal cortex and epigenetic changes in ChAT genes following adolescent intermittent ethanol exposure. - Matthew J Fecik; Polliana T Nunes; Ryan P Vetreno; Lisa M Savage (PLoS ONE)
Adolescent intermittent ethanol (AIE) exposure, which models heavy binge ethanol intake in adolescence, leads to a variety of deficits that persist into adulthood-including suppression of the cholinergic neuron phenotype within the basal forebrain. This is accompanied by a reduction in acetylcholine (ACh) tone in the medial prefrontal cortex (mPFC). Voluntary wheel running exercise (VEx) has been shown to rescue AIE-induced suppression of the cholinergic phenotype. Therefore, the goal of the current study is to determine if VEx will also rescue ACh efflux in the mPFC during spontaneous alternation, attention set shifting performance, and epigenetic silencing of the cholinergic phenotype following AIE. Male and female rats were subjected to 16 intragastric gavages of 20% ethanol or tap water on a two-day on/two-day off schedule from postnatal day (PD) 25-54, before being assigned to either VEx or stationary control groups. In Experiment 1, rats were tested on a four-arm spontaneous alternation maze with concurrent in vivo microdialysis for ACh in the mPFC. An operant attention set-shifting task was used to measure changes in cognitive and behavioral flexibility. In Experiment 2, a ChIP analysis of choline acetyltransferase (ChAT) genes was performed on basal forebrain tissue. It was found that VEx increased ACh efflux in the mPFC in both AIE and control male and female rats, as well as rescued the AIE-induced epigenetic methylation changes selectively at the Chat promoter CpG island across sexes. Overall, these data support the restorative effects of exercise on damage to the cholinergic projections to the mPFC and demonstrate the plasticity of cholinergic system for recovery after alcohol induced brain damage.